ANALISISPENDAPATAN PETANI PISANG DIDESA KANDANGTEPUS KECAMATAN SENDURO KABUPATEN LUMAJANG - Mochammad Faisal Hamzah; wahyu hidayat; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2018)
Banana is an icon from Lumajang Regency which has the largest plantation in East Java, which is in Kandangtepus Village District of Senduro Lumajang Regency. Banana is a major factor in increasing the income of banana growers. The data used in this research is Primary data which is done by structured interview. The method used in this research is multiple linier regression analysis method. Based on multiple linear regression analysis, the result of land area has a significant positive effect to farmer's income with regression coefficient of (0.327302) the number of production has a significant positive effect to farmer's income with coefficient of 0.011054 and production cost cost have positive and significant effect to farmer's income with regression coefficient of (0.594453). Hypothesis test shows the value of coefficient of determination (R2) of 0.872850.